2021
DOI: 10.3390/cells10092393
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effect of Micrornas in Extracellular Vesicles from Mesenchymal Stem Cells against SARS-CoV-2

Abstract: Extracellular vesicles (EVs) are cell-released, nanometer-scaled, membrane-bound materials and contain diverse contents including proteins, small peptides, and nucleic acids. Once released, EVs can alter the microenvironment and regulate a myriad of cellular physiology components, including cell–cell communication, proliferation, differentiation, and immune responses against viral infection. Among the cargoes in the vesicles, small non-coding micro-RNAs (miRNAs) have received attention in that they can regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
(49 reference statements)
1
28
0
Order By: Relevance
“…Since researchers predicted that the vast majority of the target genes of the detected miRNAs are related to the assembly of the viral replication machinery, and inflammatory responses, the antiviral properties of MSC-EVs were attributed to the regulatory roles of these tiny RNA molecules. In summary, these findings support the fact that MSC-EVs could represent a promising alternative to treat multiple variants of SARS-CoV-2 ( Park et al, 2021 ).…”
Section: Biomarkers and Future Therapeuticssupporting
confidence: 77%
“…Since researchers predicted that the vast majority of the target genes of the detected miRNAs are related to the assembly of the viral replication machinery, and inflammatory responses, the antiviral properties of MSC-EVs were attributed to the regulatory roles of these tiny RNA molecules. In summary, these findings support the fact that MSC-EVs could represent a promising alternative to treat multiple variants of SARS-CoV-2 ( Park et al, 2021 ).…”
Section: Biomarkers and Future Therapeuticssupporting
confidence: 77%
“…It has been proposed that miRNAs might be involved in controlling inflammation during COVID-19 (Aslani et al, 2021;Gasparello et al, 2021;Houshmandfar et al, 2021;Matarese et al, 2020;Plowman and Lagos, 2021). Theoretical CC/miRNA regulatory networks have been proposed but not validated (Khokhar et al, 2022), whereas the potential of miRNA-like therapeutics has also been suggested (Ahn et al, 2021;Dash et al, 2021;Hum et al, 2021;Park et al, 2021). Of note, initial studies have identified potential changes in miRNA expression in COVID-19 and signatures from targeted testing of 41 miRNAs have been linked to ICU treatment and mortality in a Spanish cohort (de Gonzalo-Calvo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…miR-1470 is one of the exosomal biomarkers of BMSCs for its high expression when exosomes from fibroblast serve as the control (71). Equipped with miR-92a-3p, miR-26a-5p, miR-23a-3p, miR-103a-3p, and miR-181a-5p, exosome from neuronal stem cell has therapeutic potential (78).…”
Section: The Expression Of Ncrna In Msc-origin Evsmentioning
confidence: 99%